Selective Reduction of High Alumina-Lateritic Nickel Ore (0.5 Ni-44Fe-16Al2O3) - Nurjaman, Fajar; Wahyuningsih, Wahyuningsih; Karo Karo, Pulung; Ginting, Ediman; Shofi, Achmad; Handoko, Anton Sapto (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2019)
In this present study, the effect of reductant dosage, temperature and holding time on selective reduction process of high alumina-lateritic nickel ore have been investigated clearly. The lateritic nickel ore was reduced with 5 until 15 wt. % anthracite and 10 wt. % sodium sulfate at reduction temperature of 950C, 1050C and 1150C for 60, 90, and 120 minutes. Magnetic separation process was then conducted to separate the concentrate and tailing. The analysis of reduced nickel ore is performed by the Atomic Absorption Spectroscopy, X-Ray Diffraction, and Secondary Electron Microscopy. The optimal process resulted from the reduction of nickel ore with 10 wt. % anthracite at the temperature of 1050C for 120 minutes which resulted in 0.84% nickel in concentrate. The troilite was not found in reduced ore. The iron grade increased along the increased of reduction temperature. The longer of holding time in selective reduction process increased the nickel grade but it decreased the iron grade.